A família dos números metálicos no ensino e aprendizagem de conteúdos de matemática na educação básica - Schifler, Jessica Augustin (2020)
We present in this work the family of metallic numbers, their characteristics and properties. The gold and silver numbers are the best-known members of this family, with applications in arts, architecture, engineering, music and literature. We developed workshops with students from the 6th to 9th grades of elementary school of a public school in the rural area of Mafra, Santa Catarina, introducing the metallic numbers in the study of fractions, ratios, proportions, regular polygons, irrational numbers and quadratic equations. In the activities, we combine the study of these contents with the use of technologies, such as tablets, GeoGebra and Google Sheets, in addition to videos on the subject. We conclude that metallic numbers and technological tools make it possible to contextualize the content covered, encouraging students to discuss and deepen mathematical knowledge.